The carboxy-terminal domains of erbB-2 and epidermal growth factor receptor exert different regulatory effects on intrinsic receptor tyrosine kinase function and transforming activity. - Di Fiore, P P (1990)
The erbB-2 gene product, gp185erbB-2, displays a potent transforming effect when overexpressed in NIH 3T3 cells. In addition, it possesses constitutively high levels of tyrosine kinase activity in the absence of exogenously added ligand. In this study, we demonstrate that its carboxy-terminal domain exerts an enhancing effect on erbB-2 kinase and transforming activities. A premature termination mutant of the erbB-2 protein, lacking the entire carboxy-terminal domain (erbB-2 delta 1050), showed a 40-fold reduction in transforming ability and a lowered in vivo kinase activity for intracellular substrates. When the carboxy-terminal domain of erbB-2 was substituted for its analogous region in the epidermal growth factor receptor (EGFR) (EGFR/erbB-2COOH chimera), it conferred erbB-2-like properties to the EGFR, including transforming ability in the absence of epidermal growth factor, elevated constitutive autokinase activity in vivo and in vitro, and constitutive ability to phosphorylate phospholipase C-gamma. Conversely, a chimeric erbB-2 molecule bearing an EGFR carboxy-terminal domain (erbB-2/EGFRCOOH chimera) showed reduced transforming and kinase activity with respect to the wild-type erbB-2 and was only slightly more efficient than the erbB-2 delta 1050 mutant. Thus, we conclude that the carboxy-terminal domains of erbB-2 and EGFR exert different regulatory effects on receptor kinase function and biological activity. The up regulation of gp185erbB-2 enzymatic activity exerted by its carboxy-terminal domain can explain, at least in part, its constitutive level of kinase activity.